Attitudes toward bone health among rural‐dwelling veterans identified as at risk of fracture: a qualitative analysis. (14th May 2021) - Van Tiem, Jennifer M.; Steffen, Melissa J.A.; Seaman, Aaron T.; Miller, Karla; Wardyn, Shylo E.; Richards, Christopher C.; Solimeo, Samantha L.
ABSTRACT: Although much is known about system‐level barriers to prevention and treatment of bone health problems, little is known about patient‐level barriers. The objective of this study was to identify factors limiting engagement in bone health care from the perspective of rural‐dwelling patients with known untreated risk. Over 6 months, 39 patients completed a qualitative interview. Interview questions focused on the patient's experience of care, their decision to not accept care, as well as their knowledge of osteoporosis and the impact it has had on their lives. Participants were well‐informed and could adequately describe osteoporosis and its deleterious effects, and their decision making around accepting or declining a dual‐energy x‐ray absorptiometry (DXA) scan and treatment was both cautious and intentional. Decisions about how to engage in treatment were tempered by expectations for quality of life. Our findings suggest that people hold beliefs about bone health treatment that we can build on. Work to improve care of this population needs to recognize that bone health providers are not adding a behavior of medication taking to patients, they are changing a behavior or belief. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.